2023
DOI: 10.1002/ajh.26937
|View full text |Cite
|
Sign up to set email alerts
|

Influence of racial and ethnic identity on overall survival in patients with chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is the most prevalent adult leukemia in the United States, with over 20 000 cases diagnosed annually.White patients are significantly more likely to develop CLL than other races, with incidence rates of 5.1 per 100 000 in White, 3.2 in Black, 2.1 in Hispanic, and 1.1 in Asian Americans. This amounts to a low prevalence of CLL in non-White populations, which represent between 11% and 13% of CLL patients. Due to the low incidence of CLL in non-White persons, there are minimal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…White individuals had a 1.4-fold higher incidence rate than Black individuals. 9 Although Black individuals were associated with a worse prognosis than the other races 10,11 due to the higher rate of comorbidities, 12 extra-nodal primary site involvement and advanced disease at the time of diagnosis, 11 our study emphasizes the need for increased vigilance and surveillance for CLL in both the White and Black populations for their high incidence rate and worse prognosis respectively.…”
Section: N (%)mentioning
confidence: 77%
“…White individuals had a 1.4-fold higher incidence rate than Black individuals. 9 Although Black individuals were associated with a worse prognosis than the other races 10,11 due to the higher rate of comorbidities, 12 extra-nodal primary site involvement and advanced disease at the time of diagnosis, 11 our study emphasizes the need for increased vigilance and surveillance for CLL in both the White and Black populations for their high incidence rate and worse prognosis respectively.…”
Section: N (%)mentioning
confidence: 77%
“…Furthermore, in the COVID-19 era, a high case-fatality rate and a poor response to vaccination were documented with fixed-duration and continuous treatment [104][105][106]. Overall, despite these improvements, the influence of racial and ethnic identity on OS in CLL is still significant, despite an encouraging possible reduction in the survival disparity between Black and White U.S. patients within the last 5 years [107].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the overall incidence of CLL/SLL is increasing, most rapidly in East Asia [ 7 ]. Additionally, CLL/SLL has a heterogeneous clinical course influenced by cytogenetic aberrations [ 8 , 9 ] and partly by ethnicity [ 10 , 11 ]. CLL/SLL incidence is at least a 20-fold lower in Asian countries than in Western regions, therefore, real-world data is limited, especially in Korea [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%